A novel ARCN1 splice-site variant in a Chinese girl with central precocious puberty, intrauterine growth restriction, microcephaly, and microretrognathia - Guoying Chang; Fan Yang; Lingwen Ying; Qianwen Zhang; Biyun Feng; Yao Chen; Yu Ding; Tingting Yu; Ruen Yao; Kana Lin; Juan Li; Xiumin Wang (BMC Pediatrics)
Abstract The ARCN1 gene encodes the delta subunit of the coatomer protein complex I (COPI), which is essential for mediating protein transport from the Golgi complex to the endoplasmic reticulum. Variants in ARCN1 are associated with clinical features such as microcephaly, microretrognathia, intrauterine growth restriction, short rhizomelic stature, and developmental delays. We present a case of a patient exhibiting intrauterine growth restriction, preterm birth, microcephaly, micrognathia, and central precocious puberty. Whole-exome sequencing identified a novel splice-site variant, NM_001655.5: c.1241 + 1G > A, in the ARCN1 gene. To our knowledge, this is the first documented case of ARCN1-related syndrome associated with central precocious puberty, contributing to the understanding of the disease phenotype.